Update on acquired hypogonadism in men living with HIV: pathogenesis, clinic, and treatment - De Vincentis, Sara; Rochira, Vincenzo (Frontiers in Endocrinology, 2023)
Hypogonadism is a frequent finding among men living with HIV (MLWH) and it seems to occur earlier in comparison with the general male population. Although the prevalence of hypogonadism in MLWH has significantly lowered thanks to advancements in medical management, it remains high if compared with age-matched HIV-uninfected men, ranging from 13% to 40% in the age group of 20-60 years. Signs and symptoms of low serum testosterone (T) in MLWH are cause of concern since they are non-specific, of mild-to-moderate degree, and often overlapping with those of infection per se. For these reasons, hypogonadism can be underestimated in the absence of targeted laboratory blood examinations. With regard to the etiological factors involved in the T decrease, emerging evidence has suggested the functional nature of hypogonadism in MLWH, pointing out the mutual relationship between sex steroids, health status, comorbidities, and HIV-related factors. In agreement with this hypothesis, a therapeutic approach aiming at improving or reversing concomitant diseases through lifestyle changes (e.g. physical activity) rather than pharmacological T treatment should be theoretically considered. However, considering both patient’s barriers to lifestyle changes to be maintained overtime and the lack of evidence-based data on the efficacy of lifestyle changes in normalizing serum T in MLWH, T therapy remains an option when other non-pharmacological interventions are ineffective as well as for all other functional forms of hypogonadism. From this perspective, the traditional therapeutic management of male hypogonadism in MLWH, especially the role of T supplementation, should be revised in the light of the probable functional nature of hypogonadism by considering a good balance between benefits and harmful. This narrative review presents an overview of current knowledge on hypogonadism in MLWH, deepening the factors driving and taking part in T decrease, providing advice for the clinical approach, and underlining the importance of individualized treatment aiming at optimizing non-gonadal comorbidities and thus avoiding over-, or even unnecessary, treatment with T.